THE IMPORTANCE OF CYBER PROFESSIONALISM OF A TEACHER IN THE DIGITAL TRANSFORMATION OF CAREER GUIDANCE WORK - Nazkenova Б.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article considers the importance of a teacher’s cyber-professional competence in the context of the digital transformation of career guidance. To identify the relevance of the article, a multivariate analysis of the functioning of the existing career guidance system in general secondary education was carried out. According to the survey results, traditional career guidance tools for high school students are much more popular than digital ones. This situation does not meet the modern needs of high school students in the field of career guidance and shows that teachers and psychologists are not ready to demonstrate it with the help of digital tools. Therefore, the article concludes that a cybercompetent teacher in a digital education environment should be able to meet the needs of students in the field of professionally oriented support for professional self-determination in the field of IT, STEM, STEAM and STREAM professions